Electrolyte profiles with induced hypothermia: A sub study of a clinical trial evaluating the duration of hypothermia after cardiac arrest - Kirkegaard Hans; Grejs Anders M.; Gudbjerg Simon; Duez Christophe; Jeppesen Anni; Hassager Christian; Laitio Timo; Storm Christian; Taccone Fabio Silvio; Skrifvars Markus B.; Søreide Eldar (Wiley, 2022)
Background: Electrolyte disturbances can result from targeted temperature treatment (TTM) in out-of-hospital cardiac arrest (OHCA) patients. This study explores electrolyte changes in blood and urine in OHCA patients treated with TTM.
Methods: This is a sub-study of the TTH48 trial, with the inclusion of 310 unconscious OHCA patients treated with TTM at 33°C for 24 or 48 h. Over a three-day period, serum concentrations were obtained on sodium potassium, chloride, ionized calcium, magnesium and phosphate, as were results from a 24-h diuresis and urine electrolyte concentration and excretion. Changes over time were analysed with a mixed-model multivariate analysis of variance with repeated measurements.
Results: On admission, mean ± SD sodium concentration was 138 ± 3.5 mmol/l, which increased slightly but significantly (p < .05) during the first 24 h. Magnesium concentration stayed within the reference interval. Median ionized calcium concentration increased from 1.11 (IQR 1.1-1.2) mmol/l during the first 24 h (p < .05), whereas median phosphate concentration dropped to 1.02 (IQR 0.8-1.2) mmol/l (p < .05) and stayed low. During rewarming, potassium concentrations increased, and magnesium and ionizes calcium concentration decreased (p < .05). Median 24-h diuresis results on days one and two were 2198 and 2048 ml respectively, and the electrolyte excretion mostly stayed low in the reference interval.
Conclusions: Electrolytes mostly remained within the reference interval. A temporal change occurred in potassium, magnesium and calcium concentrations with TTM's different phases. No hypothermia effect on diuresis was detected, and urine excretion of electrolytes mostly stayed low.